2020 IEEE International Conference on Power Electronics, Smart Grid and Renewable Energy (PESGRE2020) 2020
DOI: 10.1109/pesgre45664.2020.9070725
|View full text |Cite
|
Sign up to set email alerts
|

A Global Analysis on Microgrids through the PESTEL Framework

Abstract: Microgrids enable distribution of electricity with higher shares of variable renewables, higher power quality, greater reliability and higher efficiency. There are a large number of factors in addition to the technology, which affect their shift towards market competitiveness and widespread adoption. The PESTEL framework, covering Political, Economic, Social, Technical, Environmental and Legislative factors, is used to identify and describe the drivers and barriers for microgrid development at the global level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Plastic waste is a source of environmental pollution when it is produced in large quantities for a short period of time (e.g., less than 1 year) (Geyer et al, 2017) because it is hardly absorbed by microorganisms. Thus, plastic waste is disposed of in landfills, often poorly controlled, or transported to recycling channels where only a small part will be effectively recycled.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plastic waste is a source of environmental pollution when it is produced in large quantities for a short period of time (e.g., less than 1 year) (Geyer et al, 2017) because it is hardly absorbed by microorganisms. Thus, plastic waste is disposed of in landfills, often poorly controlled, or transported to recycling channels where only a small part will be effectively recycled.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Plastic waste is also a global issue because plastic waste is carried by rivers and lakes from countries' deep inlands to seas and oceans, and plastic waste then decomposes in international waters or shores up on other countries' coastlines (UNEP, 2018). The dire socioecological consequences of plastic waste, and especially plastic, are thus likely to persist because, in many parts of the world, only a tiny fraction of plastic (about 10%) is recycled, while the rest is dumped in landfills, incinerated, or released into the environment as litter (Deloitte, 2019a;Geyer et al, 2017). In contrast, steel is the most recycled material by weight, while paper has the highest recycling rate with about 66%-68%, followed by metal (32%) and glass (31%) (Bliznovska, 2023;Méndez, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dissecting RE energy cooperation between China and Philippines, Li et al used the PESTLE approach to investigate the challenges and perspectives in each country. Other studies that used the framework are found in [33][34][35][36][37].…”
Section: Extremely Strong Hindrancementioning
confidence: 99%
“…It was done using PESTAL analysis. A PESTLE analysis is a framework to analyze the key factors (Political, Economic, Sociological, Technological, Legal, and Environmental) influencing an organization from the outside [9]. It offers people professionals insight into the external factors impacting their organization.…”
Section: B Phase 2-identification Of Key Factorsmentioning
confidence: 99%